Antioxidant Potential, Acute Toxicity Profile and Bioavailability Studies of Water Soluble Analogue of Curcumin - Dr. Mohammad Haneef; Mr. Viney Budhiraja; Mr. Paras Budhiraja (International Journal of Pharma and Bio Sciences, 2022)
Curcumin, a bright yellow colored phytochemical is the principal and active ingredient - curcuminoids present in the plant Curcuma longa which belonging to the family Zingiberaceae. Curcumin has said to be metabolized in intestine and liver and metabolizes to form glucuronide and sulfate conjugate thus exhibiting its restricted oral bioavailability. It has been studied till Phase-II clinical study, but its bioavailability is still an issue (Biological Classification System-IV BCS-Class-IV). Nonetheless, curcumin can be successfully formulated for oral administration, but care needs to be taken with formulation design to ensure consistent bioavailability. There are numerous studies in support of excellent antioxidant activity, safe toxicity profile and bioavailability of conventional and modulated curcumin. The aim of the present study was to investigate the antioxidant potential, acute toxicity profile and bioavailability of water soluble part of curcumin. Objective of research is to determine the antioxidant potential and acute toxicity of aqueous soluble part of curcumin .